Associations with Meibomian Gland Atrophy in Daily Contact Lens Wearers. Issue 9 (September 2015) - Pucker, Andrew D.; Jones-Jordan, Lisa A.; Li, Wing; Kwan, Justin T.; Lin, Meng C.; Sickenberger, Wolfgang; Marx, Sebastian; Srinivasan, Sruthi; Jones, Lyndon W.
ABSTRACT Purpose To determine associations for contact lenses (CLs) and meibomian gland atrophy in a matched-pair study. Methods Contact lens wearers (case) and age- and sex-matched non–contact lens (NCL) wearers with no history of CL use (control) were recruited for a multicenter study. All subjects were administered the Ocular Surface Disease Index questionnaire and a comprehensive battery of clinical tests (e.g., tear breakup time, bulbar and limbal redness, meibography, etc.) were performed. Upper and lower eyelid meibomian gland atrophy were graded with both digital meibography (percent gland atrophy) and visual meiboscore methods. Conditional logistic regression analyses were then used to determine relationships among CL use, meibomian gland atrophy, and ocular surface signs and symptoms. Results A total of 70 matched pairs were analyzed. The mean (±SD) age of the CL group was 30.6 (±12.4) years, and that of the NCL group was 30.1 (±12.2) years. The subjects were 63% female. The association between CL wear and meiboscore was not significant univariately, but the best-fitting multivariate regression model showed that higher meiboscores were associated with being a CL wearer (odds ratio [OR], 2.45) in a model that included eyelid margin erythema (OR, 0.25) and lissamine green staining (OR, 1.25). Percent gland atrophy was not associated with CL wear in regression analysis (p = 0.31). Conclusions This study determined inconclusive associations with CLs and meibomian gland atrophy. This study also provided a comprehensive assessment of differences between CL and NCL wearers.